Does Temporary Interruption in Postsecondary Education Induce a Wage Penalty? Evidence from Canada - Bernard Fortin; Safa Ragued (Institute for the Study of Labor (IZA), 2016)
Data from the Youth in Transition Survey reveal that almost 40% of Canadian youth who left post-secondary education in 1999 had returned two years later. This paper investigates the extent to which schooling discontinuities affect post-graduation starting real wages and whether the latter are differently influenced by the reasons behind these discontinuities. We analyse this issue using data from the 2007 National Graduate Survey. We take covariates endogeneity into account using Lewbel's (2012) generated instrument approach. The source of identification is a heteroscedastic covariance restriction of the error terms that is a feature of many models of endogeneity. To allow for individual heterogeneity in the causal effect of various reasons for schooling interruption, we also provide results from two-stage quantile regressions using Lewbel's generated instruments. Conditional on the levels of schooling and experience, we find a positive effect on wages of temporary schooling interruption for men who had held a full-time job during their out-of-school spell(s). Both men and women witness a wage decrease if their interruption is associated with health issues. Women also bear a wage penalty if their interruption is due to a part-time job, to lack of money, or is caused by reasons other than health, work, and money.
Keywords: C21; C26; C31; I21; I23; I26; 330; schooling interruption; wages; temporary attrition; delayed graduation; Lewbel IV; two-stage quantile regression; Box-Cox